Exercise-Induced Plasma Metabolomic Profiles in Patients With Peripheral Arterial Disease - Semporé, Wendsèndaté Yves; Chao De La Barca, Juan Manuel; Hersant, Jeanne; Ouédraogo, Nafi; Yaméogo, Téné Marceline; Henni, Samir; Reynier, Pascal; Abraham, Pierre (Frontiers in Physiology, 2021)
Aim: A better knowledge of the biological consequences in blood of these exercise-induced ischemic events in lower extremity artery disease (LEAD) may improve the prospects of disease management. We explored the pre minus post-exercise metabolomic difference in 39 LEAD patients referred for a treadmill oximetry test (TcPO2). Methods: Ischemia was estimated through the sum of DROPs (limb TcPO2 changes minus chest TcPO2 changes) at buttocks, thighs and calves. Targeted metabolomic analyses measuring 188 metabolites were performed on a few microliters blood samples taken at the earlobe at rest and three minutes after exercise. Results: Maximum Walking Distance (MWD) was 290 [120-652] m, Ankle Brachial Index (ABI) was 0.67 ± 0.17. Supervised paired partial least squares discriminant analysis based on 23,345 models showed good predictive performance for test sets with a median area under the receiver operating characteristic (AUROC) of 0.99 and a p-value of 0.00049. The best discriminant metabolites contributing to the model included a subset of 71 (47%) of the 150 accurately measured metabolites in the plasma, comprising three acyl-carnitines, three amino acids, five biogenic amines, nine sphingomyelin, seven lysophosphatidylcholines and forty-four phosphatidylcholines. In addition, 16 of these metabolites were found to correlate with one or more severity scores of the LEAD. Conclusion: Our results provide new insights into the biological changes that accompany exercise in LEAD and contribute to a better understanding of walking impairment pathophysiology in LEAD, highlighting new candidate biomarkers.